SOCIAL MEDIA AS MALAY AND CULTURAL ART PRESERVATION: GOOGLE SCHOLAR AS REFERENCE TOOL - Haslina Husain; Mad Khir Johari Abdullah Sani; Tamara Adriani-Susetyo Salim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
In Malaysia, a diverse nation encompassing multiple ethnicities and languages, each community holds unique cultural traditions and beliefs. As responsible Malaysian citizens, it is imperative that we foster mutual respect among these various races. Malaysia places a significant emphasis on its Malay cultural heritage, featuring traditional games like Gasing, Congkak, and Wau, as well as entertainment forms such as Wayang Kuli, Dikir Barat, and Menora. These cultural elements play a crucial role in shaping the identity of the Malay youth. In the contemporary era dominated by digital technology, our generation increasingly relies on social media for various purposes. Within this context, this study focuses on exploring literature that examines the intersection of social media and the preservation of Malay cultural art. Leveraging Google Scholar as a reference tool, we aim to delve into past research that sheds light on how social media platforms contribute to the conservation of Malay cultural heritage. The study employs a methodological approach that involves identifying relevant literature from year 2017 until 2022 through Google Scholar, using keywords such as "Malay cultural art" and "social media." By undertaking this research, we seek to advance our understanding of past literature discussing the use of social media for the preservation of Malay cultural art. The findings are expected to contribute significantly to the current body of literature, serving as a valuable resource for scholars and researchers interested in this field. Ultimately, this study aims to foster awareness and appreciation for the rich cultural tapestry of Malaysia, encouraging future endeavours in preserving and promoting its diverse heritage.